Free amino acids and biogenic amines in wines and musts from - Herbert, Paulo (2010)
Characterization of musts and wines from different Alentejo sub-regions, varieties and vintages was made in terms of amino acid and amine contents, by HPLC with fluorescence detection of OPA/FMOC derivatives. The evolution of volatile and biogenic amines was also studied throughout 10 microvinifications. No significant increase in the levels of total volatile amines was observed during alcoholic or spontaneous malolactic fermentation. While higher histamine levels were only found during the storage period, an increase in the concentration of tyramine was confirmed in red wines immediately after malolactic fermentation, which seems to be also the main origin of putrescine. It was noticed that grape variety, region of production, and vintage can influence free amino acid and amine contents of musts and wines, although alcoholic and malolactic fermentations can override that effect.